2019
DOI: 10.1149/2.0661914jes
|View full text |Cite
|
Sign up to set email alerts
|

Hot Formation for Improved Low Temperature Cycling of Anode-Free Lithium Metal Batteries

Abstract: A new "hot formation" protocol is proposed to improve lower temperature cycling of lithium metal batteries. The cycling stability of anode-free pouch cells under low pressure (75 kPa) is shown to decline significantly as the cycling temperature is decreased from 40°C to 20°C. At low pressure and 40°C the initial morphology of the lithium anode is dense and columnar, far superior to that plated at 20°C. For "hot formation" two initial 40°C cycles (C/10 charge C/2 discharge) are conducted prior to extended low t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 29 publications
4
75
0
Order By: Relevance
“…This was shown to significantly improve the 20 C performance of anode-free lithium metal cells. 30 Similarly, Figure S5 shows that 20 C cycling of hybrid cells after hot formation can be sustained without increased degradation compared with cycling at 40 C.…”
Section: Electrolytes Optimization For Hybrid Cell Cyclingmentioning
confidence: 86%
“…This was shown to significantly improve the 20 C performance of anode-free lithium metal cells. 30 Similarly, Figure S5 shows that 20 C cycling of hybrid cells after hot formation can be sustained without increased degradation compared with cycling at 40 C.…”
Section: Electrolytes Optimization For Hybrid Cell Cyclingmentioning
confidence: 86%
“…[ 67 ] Genovese et al reported the effects of a “hot formation” procedure, where the initial two cycles were carried out at an elevated temperatures of 40 °C. [ 69 ] They found that the high‐temperature formation cycles enable the deposited lithium metal to form dense, columnar growths, when compared with formation cycles carried out at 20 °C. This optimized high‐temperature formation procedure was applied in anode‐free Cu || NMC pouch full cells in conjunction with 75 kPa of stack pressure to realize drastically improved performance, with over 55% capacity retention at 100 cycles compared to the same retention at only 18 cycles in cells with the formation procedure carried at room temperature (LIRR = 99.4%).…”
Section: Strategies For Improving Performance Of Anode‐free Full Cellsmentioning
confidence: 99%
“…Hot formation (>40 C) could extend cycle life to 200 cycles at 80% capacity retention combined with pressure application. [35] Pulsed charging procedures can also lead to enhanced compactness of Li metal deposition which is important in anode-free architectures. [36] A further consideration regarding the SEI formation is related to the cathode decomposition.…”
Section: Strategies To Extend Reversibility In Anode-free Cellsmentioning
confidence: 99%